Mediatization of Georgian-Indian relations at the current stage - Valentin V. Matvienko; Danara B. Kurmanova (RUDN Journal of Studies in Literature and Journalism, 2019)
The article analyzes a particular case of the mediatization of modern socio-cultural reality through the informational and communication technologies, using the example of modern Georgian-Indian relations. The authors conducted a content analysis of two leading publications in India and Georgia: the English-language newspaper “The Times of India” and the Russian-language news agency “Sputnik Georgia”, during which had studied 30 materials from the Indian media and 43 articles from the Georgian news agency published over the period January, 2013 - February, 2019. The authors concluded that the mediatization of political and economic processes in bilateral relations had required close interaction between government and the media, since a lack of information led to a distorted perception of media communications.